2020
DOI: 10.1111/1758-5899.12855
|View full text |Cite
|
Sign up to set email alerts
|

Policy Opportunities and Constraints for Addressing Urban Precarity of Migrant Populations

Abstract: Addressing sources and drivers of precarity among marginalized migrant populations in urban spaces is central to making cities inclusive, safe, resilient and sustainable for all. Yet dominant policy discourses continue to frame migrants as problematic causes of insecurity and tend to exclude them from policy processes. Deliberative democratic theory suggests that inclusive processes have the potential to create innovative solutions for resilient cities. This study elicits and reports on self‐identified sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The sources of insecurity are familiar to all precarious populations: food insecurity, access to clean environments, and a collection of processes of social exclusion. Yet they are, we suggest, amplified for migrant populations in places where they have less place attachment, limited citizenship rights, and cluster in densely populated informal settlements (Banks et al, 2011; Chu & Michael, 2019; Siddiqui et al, 2021). In effect, the study here points to a new urban precarity in that urban migration involves substituting one set of risks and vulnerabilities for a different set in the destination, which also include social factors (Siddiqui et al, 2021).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The sources of insecurity are familiar to all precarious populations: food insecurity, access to clean environments, and a collection of processes of social exclusion. Yet they are, we suggest, amplified for migrant populations in places where they have less place attachment, limited citizenship rights, and cluster in densely populated informal settlements (Banks et al, 2011; Chu & Michael, 2019; Siddiqui et al, 2021). In effect, the study here points to a new urban precarity in that urban migration involves substituting one set of risks and vulnerabilities for a different set in the destination, which also include social factors (Siddiqui et al, 2021).…”
Section: Discussionmentioning
confidence: 83%
“…For example, pollution and inadequate sanitation in densely populated areas have been found to impact migrants' health and well‐being (Adamo, 2010; McMichael et al, 2012). Furthermore, precarious livelihoods and work‐related stress factors have been linked to poor psychological well‐being outcomes among rural–urban migrants (Lu, 2010; Siddiqui et al, 2021). The observed patterns in the subjective experiences of migrants are upheld when cultural and contextual differences across the three countries are taken into account, although there is some variation in experiences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our own research in Chattogram also shows that insecure tenure, material aspects of wellbeing, access to services and labour markets and health issues associated with waterlogging and waste pollution constitute an experience of urban precarity self-identified by migrant populations (Siddiqui et al, 2019). Using survey and in-depth participatory methods, we have shown that many of these dimensions of insecurity are producing levels of mental ill-health, including reported symptoms of stress and anxiety.…”
Section: Inequality and Exclusion As Threats To Resiliencementioning
confidence: 85%